Cloning, expression, purification, crystallization and preliminary X-ray analysis of Thermus aquaticus succinyl-CoA synthetase - Joyce, Michael A. (International Union of Crystallography, 2007)
Succinyl-CoA synthetase (SCS) is an enzyme of the citric acid cycle and is thus found in most species. To date, there are no structures available of SCS from a thermophilic organism. To investigate how the enzyme adapts to higher temperatures, SCS from Thermus aquaticus was cloned, overexpressed, purified and crystallized. Attempts to crystallize the enzyme were thwarted by proteolysis of the β-subunit and preferential crystallization of the truncated form. Crystals of full-length SCS were grown after the purification protocol was modified to include frequent additions of protease inhibitors. The resulting crystals, which diffract to 2.35 Å resolution, are of the protein in complex with Mn(2+)-GDP.